CORPORATE SOCIAL NETWORKS IN EDUCATION: EXPERIENCE OF USE - Lytvynova S.; Burov O. (Kherson State University, 2017)
The paper discusses methods, forms and safety issues of social network usage for school students. Taking into consideration the growing interest of students to electronic communication in social networks (ESN), their place in the information educational environment is described. The classification of objects and use of ESNs was made to help teachers and school authority to teach students in the corporate social network. The basic components of corporate social networks (СESN) were revealed: forms of learning activity (individual, group, and collective), forms of learning organization (quiz, debates, discussions, photo-story, essay contest, a virtual tour, mini design web quest, and conference video-lesson), and database. Particular aspects of the use of certain forms for students training in ESN aсcording to the type of social objects (messages, individual messages, video files, photos, audio files, documents, comments, and blitz-survey) were defined. Student safety when using ESN and СESN impact on a student social and cultural intelligence development are discussed as well.